Medication concordance in modern medicine – A critical appraisal from an Indian perspective - Atal, Shubham (J Family Med Prim Care, 2019)
Modern medicine encompasses a holistic approach toward patient care that seeks to integrate the social, psychological, and pathological aspects of a disease. In line with this, the traditional model of improving treatment outcomes through improved compliance or adherence has given way to the concept of “concordance” that respects the integrity of the patient, autonomy, and self-determination. A self-conscious patient actively and equally participating in her or his comprehensive healthcare can bring a paradigm shift in the perceptions and functioning of the healthcare sector. Medication concordance can be expected to play a key role in improving patient well-being, clinical outcomes, and healthcare delivery. However, it is fraught with numerous questions to be addressed ranging from lack of clarity or standard protocol, medicolegal intricacies, cultural–linguistic barriers, illiteracy, shortage of time, infrastructure, and manpower. There are major challenges in the effective implementation of this initiative which has definite potential to prove beneficial in Indian healthcare settings. The success of this novel approach can only be accomplished by coordinated, inclusive, and persistent efforts from all participants of healthcare with fostering of a milieu of trust, belief, and communication. A systematic literature search was conducted using key words from relevant articles and MeSh terms on Google Scholar and PubMed. Data were abstracted according to their relevance to subheadings of the review and synthesis of concepts was done through multiple reviews by atleast two reviewers for any subsection.